THE ANALYSIS ON FACTORS INFLUENCING THE LEARNING OUTCOME ON MICROECONOMICS USING CONFIRMATORY FACTOR ANALYSIS MODEL - Luthfiya Fathi Pusposari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The research aims to identify factors influencing the learning outcome on microeconomics theories of social education students of UIN Malang. Theoretically, factors influencing learning outcomes are varied. Therefore, the researcher collaborates some opinions on factors influencing learning outcomes, and the process generates 25 subfactors. The research employs a quantitative descriptive method. The data was collected using questionnaires of the Likert scale and distributed to all research subjects. The researcher employed a confirmatory analysis model to analyze the data. The result showed that there are seven factors influencing learning outcomes on the economy subject: 1). The ability of students and lecturer related to the element on background knowledge, teaching method, course interest, learning manner, lecturer’s explanation; 2). The Learning method about student learning style, learning the habit, and determining intensity; 3). The Students’ initial modal formed by factors such as previous experience, talent, benefit, and intelligence; 4). The variable of sex and age creates the readiness factor; 5). The facility factor formed by the variable of classroom facilities and the financial situation; 6). The moral condition and family support create the psychology factor; 7). The last element is learning drive is formed by the variable of recitation and motivation.